Developing Robust Standardised Analytical Procedures for Cannabinoid Quantification: Laying the Foundations for an Emerging Cannabis-Based Pharmaceutical Industry - Matthew T. Welling; Lei Liu; Arno Hazekamp; Ashley Dowell; Graham J. King (Medical Cannabis and Cannabinoids)
The plant genus Cannabis is a prolific producer of unique pharmaceutically relevant metabolites, commonly referred to as cannabinoids. Robust and standardised methods for the quantification of cannabinoids within botanical and drug forms is a critical step forward for an emerging Cannabis-based pharmaceutical industry, which is poised for rapid expansion. Despite a growing body of analytical methods for the quantification of cannabinoids, few have been validated using internationally accredited guidelines. Moreover, standardised methods have yet to be developed for application at various stages of manufacture as well as for different levels of processing and refinement. Validation parameters for establishing robust standardised methods for cannabinoid quantification within Cannabis-based drug forms are critically discussed. Determining an appropriate level of specificity (discrimination) among heterogeneous botanical matrices as well as evaluating accuracy (recovery) and inter-laboratory precision (reproducibility) within strict and volatile regulatory environments are potential obstacles to the establishment of robust analytical procedures. We argue that while some of these challenges remain unique to Cannabis, others are common to botanical-based drug development and manufacture. In order to address potential barriers to analytical method standardisation, a collaborative research initiative inclusive of academic and commercial stakeholders is proposed.